2017
DOI: 10.1097/md.0000000000007193
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive mitral valve replacement is a safe and effective surgery for patients with rheumatic valve disease

Abstract: The aim of the study was to evaluate the treatment of minimally invasive mitral valve replacement (MIMVR) through a right minithoracotomy for patients with rheumatic mitral valve disease.From February 2009 to December 2016, 360 patients with rheumatic mitral valve disease underwent mitral valve replacement by the same surgeon. Among them, 150 patients accepted MIMVR through a right minithoracotomy, whereas the other 210 accepted a traditional median sternotomy. After matching by patients by age, sex, EuroSCORE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…We experienced one case of mitral annulus rupture while performing valve replacement via the minimally invasive approach, this has been reported elsewhere [9]. Zhai et al also reported two cases of cardiac rupture in a population undergoing minimally invasive mitral surgery, both patients died [10]. On the other hand, PPM was also reported in patients with mitral valve replacement.…”
Section: Discussionsupporting
confidence: 66%
“…We experienced one case of mitral annulus rupture while performing valve replacement via the minimally invasive approach, this has been reported elsewhere [9]. Zhai et al also reported two cases of cardiac rupture in a population undergoing minimally invasive mitral surgery, both patients died [10]. On the other hand, PPM was also reported in patients with mitral valve replacement.…”
Section: Discussionsupporting
confidence: 66%
“…We experienced one case of mitral annulus rupture while performing valve replacement via the minimally invasive approach, this has been reported elsewhere (9). Zhai et al also reported two cases of cardiac rupture in a population underwent minimally invasive mitral surgery, both patients died (10). On the other hand, PPM was also reported in patients with mitral valve replacement.…”
Section: Discussionmentioning
confidence: 90%
“…In spite of the improvement in healthcare and living standards in recent years, rheumatic fever is still endemic among Egyptian population. Rheumatic valvular lesions are thick and cause calcification and adhesion of valve leaflets, so their surgical manipulation is difficult, in comparison with other pathologies [7]. All our patients had rheumatic mitral valve disease, while previous studies focused mainly on patients having a degenerative disease or mixed pathology.…”
Section: Discussionmentioning
confidence: 98%
“…[8]. Few recent minimally invasive studies were reported on rheumatic valves; Junyu Zhai, and associates [7], a Chinese study that used thoracoscope for removal the damaged native mitral valve only; Vivek Kanhere and colleagues [9], an Indian study without video assistance and Noedir Antonio and associates [10], a Brazilian study used thoracoscope mainly for commissurotomy of stenotic mitral valve. The procedure was technically feasible in all our cases, with mean operative, ischemic and bypass times that were comparable to those reported by other studies [11].…”
Section: Discussionmentioning
confidence: 99%